PENGARUH KOMPETENSI KERJA, PELATIHAN KERJA, DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KEJAKSAAN NEGERI PIDIE, ACEH - Presilawati, Febyolla; Fatma, Surya; Adira, Riska Ayu (JSI: Jurnal Saudagar Indonesia, 2024)
The aim of this research is to determine the influence of work competency, work training and work environment both simultaneously and partially on employees at the Pidie Prosecutor's Office. Data collection method is through a list of questions/questionnaires and documentation studies. The objects of this research are employees of the Pidie Prosecutor's Office. The sample for this research was 33 respondents. The data analysis method uses multiple linear regression analysis. The results of the research show that in a simultaneous test the influence variables of work competency, work training and work environment have an effect on employees with a value of Fcount (90.093) greater than Ftable (2.911). Work competency has a partial effect on employees with the tcount value (2.326) being greater than the ttable value (2.040). Job training has a partial effect on employees with the tcount value (3.033) being greater than the ttable value (2.040). The work environment has a partial effect on employees with the tcount value (4.372) being greater than the ttable value (2.040). The correlation coefficient (R) value is 94.7%, which means it has a very strong relationship with employees. Meanwhile, the coefficient of determination (R2) obtained was 88.7%, while the remaining 11.3% was explained by other factors such as organizational culture, work discipline and job satisfaction.Keywords: Competency, Work Training, Work Environment, Employee Performance